VALIDITAS DAN RELIABILITAS ANGKET KETERAMPILAN SOSIAL ANAK USIA DINI - Fitri Handayani; Heris Hendriana; Wiwin Yuliani (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
Early Childhood has characteristics that are characteristic include physically, socially, morally and etc. Childhood is also called the golden age which is very important for all of its life as a time of foundation formation and personality foundation that will determine the child's experience in the next life. One of the aspects developed in Early Childhood Education is the Social Emotional Aspect, one of which is related in Social Skills. To know the potential that early childhood has related to social skills, it’s important to have an instrument or measuring instrument in the form of a questionnaire. Instrument is a tool used as a tool to measure an object or collect data from a variable. An instrument is said to be good when valid and reliable. Therefore, this study aims to test the Validity and Reliability of Early Childhood Social Skills with the research TKQ Al Hasan Bandung students numbered 13 students. Validity test results are obtained in a low category, which means that polls that have been compiled tend to show results that change if tested again at different times and subjects.  Keywords:  Early Childhood, Social Skills, Validity and Reliability